High-resolution varve sequences record one major late-glacial ice readvance and two drainage events in the eastern Lake Agassiz-Ojibway basin. (1st November 2019) - Godbout, Pierre-Marc; Roy, Martin; Veillette, Jean J.
Abstract: Lake Ojibway developed at the southern Laurentide Ice Sheet margin during the last deglaciation and covered vast expanses of northeastern Ontario and northwestern Quebec (Canada). The late-stage history of the lake is complex, presumably marked by a coalescence with Lake Agassiz and by late-glacial ice readvances into the basin shortly before its final drainage∼ 8200 years ago. However, these events are poorly defined in the Lake Ojibway varve record. Here we present evidence for the occurrence of one major ice readvance and two distinct drainage events from two varve sequences in northwestern Quebec. The Matagami section contains 231 varves that comprise an interval recording a late-glacial (Cochrane) ice readvance. The La Reine section spans 100 varves and the base of the sequence is characterized by a set of chaotic and coarse-grained (silty) rhythmites that marks the first lake drainage. These bottom rhythmites are overlain by a set of 65 thick varves, which are in turn capped by a thick silt bed associated with the final drainage of Lake Ojibway. Varve thickness measurements allow the correlation of these sections with the main Ojibway varve record that spans∼ 2129 years in the region (where varve 1 represents the start of sedimentation). The Matagami sequence covers varve years 1644–1874 and the onset of the Cochrane readvance occurred in varve year 1817. The lower part of the La Reine sequence below the bottom chaotic rhythmites was deposited between varve years 1843–1877, while the overlying set of thick varves is correlated to varve years 2065–2129, thus indicating a hiatus of 188 varves. The distinct thick varves show strong compositional and stratigraphic similarities with the Connaught sequence reported elsewhere in the basin and point to a connection with the late-glacial (Cochrane) ice dynamics, which appear to have played an important role on the lake evolution. These results indicate that the late-stage history of Lake Ojibway was marked by the already known Cochrane major ice readvance which was followed by two drainage events separated by at least 65 years, consistent with North Atlantic sediment records that document a two-step drainage of Lake Agassiz-Ojibway. Highlights: Two new varve sequences and available varve records document the late-stage lake history. Compositional varve data confirm the occurrence of one synchronous basin-wide ice readvance. The Cochrane ice readvance occurred ∼310 years before the final drainage of the lake. One varve sequence comprises two lake drainage units separated by 65 years. This is the first continental evidence for a two-step drainage of Lake Agassiz-Ojibway.